Authentication of chicken-derived components in collagen-containing foods using natural macromolecular marker fragments by LC-MS method. (March 2023) - Deng, Guiya; Jiang, Xianchao; Song, Zihao; Li, Chengming; Guan, Yuepeng; Guo, Shangwei; Huang, Yaqin
Abstract: Collagen is a biopolymer in animals that has been widely used in the food field to improve the value of health benefits in products. Chicken skin, which is a collagen-containing food, is popular as a healthy fat replacer for processed meat. To enable high information transparency of the products, the chicken-derived components need to be traceable to guarantee food safety and quality. However, the current methods for identifying the chicken-derived components in food still lack accuracy. Here a combination of two marker peptides were discovered and employed to establish a sensitive method based on LC-MS for the detection of chicken-derived components in collagen-containing foods. This method has a very low detection limit of 0.33 pg and 0.16 pg for two marker peptides, respectively. The results illustrated that the combination of these maker peptides could be utilized for the authentication of the chicken skin-derived components in processed meat. Graphical abstract: Image 1 Highlights: Two marker peptides have been identified from chicken skin collagen. Chicken skin collagen can be sensitively detected by the peptides at low limit of detection. Chicken skin adulterated in minced meat can be detected accurately.